(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This publication examines two principal techniques of fibre laser marking on copper and brass substrates, focusing on the achievement of both dark and white (light) markings. It investigates the effects of marking speed, power density, frequency, and raster pitch on marking contrast. The study identifies the power density threshold that distinguishes between light and dark markings, determining the experimental critical power density for melting at varying speeds for both materials. It also compares experimental values with theoretical predictions of critical melting power density. The findings offer practical recommendations for optimizing laser parameters to achieve high-contrast markings, thereby enhancing traceability and quality control in industrial applications involving copper and brass components.